Simultaneous Quantification of 17 Cannabinoids by LC–MS-MS in Human Plasma. Issue 4 (23rd March 2021) - Sempio, Cristina; Almaraz-Quinones, Nohemi; Jackson, Matthew; Zhao, Wanzhu; Wang, George Sam; Liu, Ying; Leehey, Maureen; Knupp, Kelly; Klawitter, Jelena; Christians, Uwe; Klawitter, Jost
Abstract: In recent years, the surge in use of tetrahydrocannabinol (THC) and cannabidiol (CBD) has increased the need for sensitive and specific analytical assays to measure the said compounds in patients, to establish dose–effect relationships and to gain knowledge of their pharmacokinetics and metabolism. We developed and validated an online extraction high-performance liquid chromatography-tandem mass spectrometry (HPLC–MS-MS) method for simultaneous quantification of 17 cannabinoids and metabolites including THC and its metabolites, CBD and its metabolites and other minor cannabinoids in human plasma. CBD-glucuronide (CBD-gluc) standard was produced in-house by isolation of CBD-gluc from urine of patients using pure CBD oil. For calibration standards and quality control samples, human plasma was spiked with cannabinoids at varying concentrations within the working range of the respective compound and 200 µL of the plasma was extracted using a simple one-step protein precipitation procedure. The extracts were analyzed using online trapping LC/LC–atmospheric pressure chemical ionization–MS-MS running in the positive multiple reaction monitoring mode. The lower limit of quantification ranged from 0.78 to 7.8 ng/mL, and the upper limits of quantification were between 100 and 2, 000 ng/mL. Inter-day analytical accuracy and imprecision ranged from 90.4% to 111% and from 3.1% to 17.4%, respectively. The analysis of plasma samples collected during clinical studies showed that (3R- trans )-cannabidiol-7-oic acid (7-CBD-COOH) was the major human metabolite with 5960% (59.6-fold) of CBD followed by 7-hydroxy-CBD (177%), CBD-gluc (157%) and 6α-hydroxy-CBD (39.8%); 6β-hydroxy-CBD was not detected in any of the samples. In the present study, we developed and validated a robust LC–MS-MS assay for the simultaneous quantification of cannabinoids and their metabolites, which has been used to measure >5, 000 samples in clinical studies. Moreover, we were able to quantify CBD-gluc and showed that 7-CBD-COOH, 7-hydroxy-CBD and CBD-gluc are the major CBD metabolites in human plasma.